EFFECT OF DEPOSITION TECHNIQUES OF REINFORCEMENT DURING FABRICATION OF AL-BASED SURFACE HYBRID MATRIX METAL MATRIX COMPOSITE - et. al., Kuldip Kumar Sahu, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Several deposition methods have been proposed for pre-deposition of reinforcement particle for preparation of surface metal matrix composite by Friction Stir Process. The method, which will effectively and homogeneously spread the reinforcement within processed zone, will be considered as best possible method.Homogeneous volumetric metal matrix composites can be fabricated by conventional casting and modified stir casting methods. Friction stir process (FSP) can be used as one of the best technique to fabricate surface modified metal matrix composites. In this research article, silicon carbide and graphite powder are used as reinforced materials and AA6061 is used as parent metal matrix material. FSP which is a versatile surface composite preparation technique is applied for fabrication of surface composite. Herein, single channel, multi-channel and perforated holes methods have been utilized for reinforcement deposition. As per the results, perforated blind holes method is reported as best method of pre deposition of powders. Finally, array of holes for pre-deposition of reinforcement powder improves approx 25% in ultimate tensile strength , 40% in micro-hardness and appreciable grain refinement are observed in metal matrix composite processed by FSP as compared to as received alloy.